Response of Microbial Community Structure and Diversity to Nitrogen Deposition in Soils of Pinus yunnanensis Forest of the Central Yunnan Plateau - SONG Chenggong; WANG Keqin; SONG Yali; LI Xiaodong; ZHANG Jiguo; LI Yun; DENG Qiujiang (Shuitu Baochi Xuebao)
[Objective] To study the characteristics of changes in chemical properties and diversity and structural composition of soil microbial communities in Pinus yun-nanensis soils on the Central Yunnan Plateau under nitrogen deposition, and to analyze the correlation between soil microorganisms and soil chemical properties, in order to provide a scientific basis for understanding the trend of changes in nutrient cycling in forest soil ecosystems under nitrogen deposition and observing soil microbiological changes. [Method] The soil of P. yunnanensis forests on the Central Yunnan Plateau was selected as the research object, CO(NH2)2 was used as the N source, and four different gradients were set up for simulated N deposition experiments, including control CK [N 0 g/(m2·a)], low nitrogen LN [N 10 g/(m2·a)], medium nitrogen MN [N 20 g/(m2·a)], and high nitrogen HN [N 25 g/(m2·a)], the structure and diversity of soil bacterial and fungal community were analyzed, and the characteristics of the changes of soil pH, TOC, TN, TP, NH+4-N and NO-3-N were determined. [Results] (1) In both the dry and rainy seasons, soil pH and TOC content were reduced, and TN was increased under each N treatment when compared with CK, and both NH+4-N and NO-3-N were increased at MN and HN compared to CK; (2) Both bacterial and fungal α-diversity were higher in the rainy season than in the dry season; bacterial α-diversity increased at LN under both seasons compared to CK, whereas fungi α-diversity increased at LN in the dry season; (3) In both the dry and rainy seasons, the dominant bacterial phyla were Proteobacteria, Acidobacteria and Actinobacteria, and the dominant fungal phyla were Basidiomycota, Ascomycota and Mortierellomycota; (4) The dominant bacterial and fungal genera were significantly correlated with pH, TOC, TN and NH-3-N during the dry and wet seasons. [Conclusion] Nitrogen deposition can provide soil microorganisms with effective nutrients such as NH+4-N and NH-3-N, but soil acidification due to nitrogen deposition can reduce soil TOC content and affect the structure of soil microbial communities.